Peculiarities of the Functioning of the Circulation System in Rower Athletes Hot Climate - Xujabekov M.A; Kuziev M.S. (Zien Journals, 2023)
This in the article of students knowledge activity increase, independence role increase and creative thinking ability in raising STEAM technologies study in the process of application features and benefits given is this technology modern at school of application important aspects set given
Keywords: STEAM; Education efficient teaching method